Comparative assessments of machining forces in 3D printed polymer composite during milling operation using two coated carbide end mills. (2022) - Das, Anshuman; Barrenkala, Dineshwar; Debnath, Kishore; Kumar, Pawan; Rajan, Raman; Patel, Saroj Kumar
Abstract: The composites of carbon fiber reinforced polymer (CFRP) are rapidly turning into the most extensively used material in aerospace and automotive applications due to their superior corrosion-resistant exterior and ratio of strength-to-weight. The flexibility to fabricate complex shapes and alter the fiber orientation of CFRP composites via three-dimensional (3D) printing or additive manufacturing is gaining prominence. However, because of their anisotropic and heterogeneous structure these composites were regarded as the difficult-to-cut materials. The parts made out of these composites are often made to near-net shape in astronautic and aerospace industry. However, part finishing typically necessitates post-process machining such as milling, in order to satisfy dimensional accuracy prior to assembly. The aim of this thesis is to explore the machinability aspects in terms of machining forces 3D printed CFRP composites by milling CFRP employing TiAlCrN and hard carbon coated solid carbide end mills in dry cutting environments. A 3D printed multidirectional CFRP workpiece was fabricated using a Mark forged industrial printer and milling operations were carried on additively manufactured workpiece with two distinct coated tools according to the experimental design created on Taguchi's L16 orthogonal array in which three variables namely feed rate, depth of cut, spindle speed were altered at four distinct levels. With TiAlCrN coated carbide tool, least machining forces observed compared to hard carbon coated carbide tool.